The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/10409289.2016.1255080
|View full text |Cite
|
Sign up to set email alerts
|

Effortful Control and Academic Achievement in Rural China

Abstract: Research Findings: This study investigated the relationships between effortful control and early literacy and mathematics achievement. A total of 181 children (85 girls and 96 boys) from rural China were assessed when they were in Grades 1 and 2. Path analyses controlling for maternal education indicated that effortful control at the beginning of Grade 1 predicted incremental achievement in literacy and mathematics at the end of Grade 1 and mathematics achievement at the end of Grade 2. Growth in effortful con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Concurrent and predictive associations between EF and math and EF and literacy have been supported by international research in countries, such as Germany, Portugal, India, Kenya, Ghana, China, Taiwan, Italy, the United Kingdom (U.K.), and the United States (U.S.; Bhavnani et al, 2019 ; Cadima et al, 2015 ; De Franchis et al, 2017 ; Gathercole et al, 2004 ; von Suchodoletz & Gunzenhauser, 2013 ; Wanless et al, 2011; Willoughby et al, 2019 ; Zhang & Rao, 2017 ). There is also convergent evidence of positive associations between EF and early academic skills in cross-cultural research, indicating this finding is likely not culture or country specific (Wanless et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Concurrent and predictive associations between EF and math and EF and literacy have been supported by international research in countries, such as Germany, Portugal, India, Kenya, Ghana, China, Taiwan, Italy, the United Kingdom (U.K.), and the United States (U.S.; Bhavnani et al, 2019 ; Cadima et al, 2015 ; De Franchis et al, 2017 ; Gathercole et al, 2004 ; von Suchodoletz & Gunzenhauser, 2013 ; Wanless et al, 2011; Willoughby et al, 2019 ; Zhang & Rao, 2017 ). There is also convergent evidence of positive associations between EF and early academic skills in cross-cultural research, indicating this finding is likely not culture or country specific (Wanless et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…When the related literature is examined, it is seen that in studies in which children's effortful control is determined with scores obtained from teachers, an examination of the relationship of the subdimensions of effortful control with early academic competence and early academic enablers is overlooked. Researchers are generally revealed to have examined total scores calculated for effortful control in its relationship with academic skills (e.g., Blair & Razza, 2007;Fabes et al, 2003;Jahromi et al, 2017;Zhang & Rao, 2017). Moreover, in the study, in the relationship of behaviour regulation with early academic competence and early academic enablers, the subdimensions of early academic competence and early academic enablers are examined one by one.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence has shown that effortful control is positively associated with student engagement, including emotional engagement (Valiente, Lemery‐Chalfant, & Castro, ), cognitive engagement (Blair & Razza, ), and behavioral engagement (M. Wang et al, ). In addition, effortful control is typically associated with math ability (Blair, Knipe, & Gamson, ; Sánchez‐Pérez, Fuentes, Pina, López‐López, & González‐Salinas, ; Swanson et al, ; Zhang & Rao, ). It suggests that effortful control may be important in improving mathematical abilities through the active engagement in math learning activities.…”
Section: The Present Studymentioning
confidence: 99%